P024 Children's sleep and fathers' health and wellbeing: a systematic review. (7th October 2021) - Coles, L; Thorpe, K; Smith, S; Hewitt, B; Ruppanner, L; Bayliss, O; O'Flaherty, M; Staton, S
Abstract: Introduction: Night-waking is typical across infancy and early childhood. Although mothers are traditionally primary carers for children overnight, child sleep may impact others in the household, such as co-dwelling fathers. Despite expectations of more 'hands on' fathering, the relationship between children's sleep and fathers' health and wellbeing has not been previously synthesised. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement and registered with the Prospective Register of Systematic Reviews (PROSPERO). Focusing on fathers, this review synthesised evidence pertaining to effects of children's sleep (from birth to 12 years) on fathers' health and wellbeing. Results: From 4, 421 records, 29 studies met inclusion criteria. Findings showed: (1) child sleep was associated with father's sleep when child sleep was measured through father-report or objective measurement; (2) poorer child sleep was associated with poorer general health and wellbeing among fathers, however, associations of poor child sleep with depression were fewer; and (3) poor child sleep was negatively associated with quality of within-couple and parent-child relationships. Discussion: Results suggested two principal issues: (1) Systematic variation in measures and findings underscores importance of objective measurement. Yoked actigraphy techniques are vital for understanding inter-relationships of family sleep and attendant outcomes. (2) Different patterns of child sleep and parent outcomes suggest direct and indirect pathways of effect. Understanding patterns of overnight caregiving, and factors underpinning parent decisions, are important for understanding mechanisms linking child sleep to fathers' outcomes and for designing effective interventions to support parents.